ANALISIS PENGARUH BI RATE, RETURN ON ASSET, DAN RETURN ON EQUITY TERHADAP RETURN SAHAM PT TAMBANG BATUBARA BUKIT ASAM (PERSERO) TBK. PERIODE 2007-2011 - Prakoso, Dennis Nugroho; Boentoro, Sinta (Jurnal Manajemen, 2013)
This research is conducted to find out the influence of BI Rate, Return On Asset, and Return On Equity on share return of PT Tambang Batubara Bukit Asam (Persero) Tbk. Data gathered is time series data which is analyzed by using GARCH method. The result indicate that only BI Rate has a significant effect.Key Words: BI Rate, Return On Asset, Return On Equity, Return